MORPHOMETERIC ANALYSIS OF NORMAL RENAL DIMENSIONS IN ADULTS BY MULTIDETECTOR COMPUTERIZED TOMOGRAPHY SCAN - Maria Mohiuddin; Arsalan Manzoor; Muhammad Ali; Nuzhat Hassan (ziauddin University, 2024)
Background: Kidney dimensions are influenced by different factors such as side, age, gender and geographical location. Thus, the purpose of our study was to determine reference range of kidney dimensions and effect of age, gender and side on renal dimensions in adults in a subset of Karachi population. Methods: The study was conducted from December, 2016 to May, 2017 in the department of Radiology, Ziauddin Hospital, Clifton Campus, Karachi. A total of 250 individuals (129 males and 121 females) aged 21 to 60 years without known renal disease were included in the study. Study participants were those who presented to Radiology Department with non-renal disease for abdominal contrast computerized scan. All individuals were categorized according to gender and age. Statistical analysis was done on Statistical Package for Social Sciences (SPSS) version 20. Independent sample T test, one way ANOVA and Pearson's correlation analysis were applied. P- value of ≤ 0.05 was considered significant. Results: Mean right renal length, width and anteroposterior thickness were 10.81±0.71 cm, 4.77±0.23 cm and 4.36±0.21cm respectively. Mean left renal length, width and anteroposterior thickness were 11.12±0.73 cm, 4.84±0.23 cm and 4.44±0.19 cm respectively. Mean volume of right and left kidneys were 118.80±17.98 cm3 and 126.00±18.36 cm3 respectively. A significant difference (p=0.001) was found between right and left kidney dimensions. A weak positive correlation of mean renal volume of both kidneys was observed between males and females (right renal volume r=0.024, left renal volume r=0.035). While a significant moderate negative correlation was seen between mean renal volume and age (right r= -0.456, p < 0.001: left r= -0.462, p < 0.001). Conclusion: This study presents a reference range of renal dimensions in adults without known renal disease in a subset of Karachi population. It is concluded that renal dimensions and renal volume varies significantly with side of kidney, gender and age. Key Words: Kidney, Gender, Adult, Tomography